Improvement of the Frying Quality and Storage Stability of the Sudanese Groundnut Oil - Mohammed Ali, Dena Omer; R. Ahmed, Abdel Halim; Mohammed, Babiker E. (Pakistan Journal of Nutrition, 2011)
The improvement of the frying quality and storage stability of the groundnut oil by adding 30% palm olein were studied during the frequent frying and different storage periods: 12 days, 40 days and 96 days at room temperature (37±3oC). The physiochemical parameters used in this study showed significant (p<0.05) changes in the viscosity of the ground oil and the oil blend during the frequent frying but after 40 days of storage the viscosity of the 2 samples was decreased and then increased by the end of the storage (96 days). Also the results showed significant (p<0.05) increase in the free fatty acid during the frying and the three periods of storage. However the Peroxide Value (P.V) increased significantly (p<0.05) during the 4th time of frying from 11.167 mqu/kg to 31.00 and from 11.933 to 21.200 for the groundnut oil and the oil blend respectively the increase in the (P.V) continued up to the end of the storage for the both samples but the oil blend recorded the lower values from 31.100 mequ/kg to 148.100 and from 21.867 to 41.100 for the groundnut oil and the oil blend respectively. On the other hand, the Polymer Content (P.C) of the 2 samples was found to increase significantly (p<0.05) from 0.537-2.440% and from 0.437-1.383% for the groundnut and the oil blend respectively, these values during the frequent frying, wear as during the storage the P.C continued to increase till recorded 7.773% and 6.450% for the groundnut oil and the oil blend respectively in general, the results obtained in this study indicated that adding palm olein to the groundnut oil at a ratio of 70% groundnut oil 30% palm olein greatly improved the frying quality and storage stability of the latter oil.